Interfacial transition zone modelling for characterisation of masonry under biaxial stresses - Zahra, Tatheer; Jelvehpour, Ali; Thamboo, Julian A.; Dhanasekar, Manicka (Construction & building materials, 2020)
•RVE developed previously is enriched with Interfacial Transition Zones (ITZ).•ITZ incorporates gradually varying properties of interface between constituents.•ITZ enriched RVE predicts biaxial failure envelopes of masonry quite well.•ITZ eliminates need for contact interface or interface element modelling.•ITZ enriched RVE can be incorporated into multiscale modelling of masonry walls. This paper presents a concept of Interfacial Transition Zone (ITZ) enrichment for the characterisation of masonry under biaxial stress states to a nonlocal transient damage representative volume element (RVE) model developed by the authors (Jelvehpour et al., 2019). ITZ enrichment has been realised through a series of transition layers on either side of the unit – mortar interface with gradually varying properties of the constituent materials so that weaker mortar – stronger brick and stronger mortar – weaker brick combinations can be considered. Two model parameters, viz., the thickness and the stiffness degradation of the ITZ have been introduced to control the thickness and stiffness degradation of the transition layers; these parameters have been calibrated to fit the experimental data available in the literature. The calibrated ITZ enriched RVE model was then applied to conventional clay brick, concrete block and drystack (mortarless) masonry by simulating the experimental tests reported in the literature; good agreement was obtained. The RVE was then applied to predict the failure envelope of various masonry types subject to biaxial stress states. The ITZ enriched RVE eliminates the need for introduction of either interface element or contact nonlinearity between the masonry unit and the mortar or between drystack masonry units with wide ranging benefits of analysing masonry structures under various load cases.